Edukasi tentang Keselamatan dan Kesehatan Kerja pada Pekerja di Proyek Perbaikan Gedung Sekolah X di Jakarta - Jannah, Farahul; Khoiriyah, Rizqiyani (Jurnal Abdimas Kesehatan (JAK), 2024)
The construction work sector is one of the work sectors that has a high risk of experiencing work accidents because work in this sector uses a lot of machines, materials, workplaces, and a dangerous work environment. Many workers in this sector do not know and understand about occupational safety and health (OHS), while OHS knowledge is a basic need for construction workers. Without basic knowledge of OSH, workers will not realize that there are many hazard factors that can cause accidents or work-related illnesses. This Community Service activity is expected to enable workers to recognize dangerous factors in the workplace and how to control them to minimize the occurrence of work accidents. Educational activities about occupational safety and health for construction workers were held for construction workers on the X school building renovation project in Jakarta, totaling 15 workers. After this activity is held, workers can understand K3, such as the definition and objectives of K3, definition of hazards and risks, risk control and are able to identify hazards in their current work. In the future, it is hoped that K3 training will be held with a more specific theme regarding construction work